Validation of biomarkers for loin meat quality (M. longissimus) of pigs. (8th February 2014) - Pierzchala, M.; Hoekman, A.J.W.; Urbanski, P.; Kruijt, L.; Kristensen, L.; Young, J.F.; Oksbjerg, N.; Goluch, D.; te Pas, M.F.W.
Summary The aim of this study was to validate previously reported associations between microarray gene expression levels and pork quality traits using real‐time PCR. Meat samples and meat quality data from 100 pigs were collected from a different pig breed to the one tested by microarray (Large White versus Pietrain) and a different country of origin (Denmark versus Germany). Ten genes (CARP, MB, CSRP3, TNNC1, VAPB, TNNI1, HSPB1, TNNT1, TIMP‐1, RAD‐like) were chosen from the original microarray study on the basis of the association between gene expression levels and the meat quality traits meat %, back fat, pH24, drip loss %, colour a*, colour b*, colour L*, WB‐SF, SFA, MUFA, PUFA. Real‐time PCR detection methods were developed for validation of all ten genes, confirming association with drip loss (two of two genes), ultimate pH (three of four genes), a* (redness) (two of six genes) and L*(lightness) (two of four genes). Furthermore, several new correlations for MUFA and PUFA were established due to additional meat quality trait information on fatty acid composition not available for the microarray study. Regression studies showed that the maximum explanation of the phenotypic variance of the meat quality traits was 50% for the ultimate pH trait using these ten genes only. Additional studies showed that the gene expression of several of the genes was correlated with each other. We conclude that the genes initially selected from the microarray study were robust, explaining variances of the genes for the meat quality traits.